Assessment of structural changes in the left atrium myocardium according to cardiac magnetic resonance with contrast before and after balloon cryoablation in patients with persistent atrial fibrillation - O. V. Stukalova; V. S. Kirilova; O. P. Aparina; E. B. Maykov (Евразийский Кардиологический Журнал)
Aim. To study the structural changes of the left atrium myocardium according to magnetic resonance imaging with contrast in patients with persistent atrial fibrillation before and after balloon cryoablation and compare the results with the effectiveness of the intervention.Material and methods of research. The study included 28 patients with persistent form of atrial fibrillation. All patients before and after magnetic resonance imaging underwent cardiac magnetic resonance imaging with delayed contrast using a high-resolution MR pulse sequence (voxel size 1,25x1,25x1,25 mm) before and after cryoablation.The severity of atrial fibrous lesion was calculated automatically using a specialized LGE HEART Analyzer program using algorithms based on the myocardial contrast index with a threshold value of 1.38. The clinical efficacy of the intervention was evaluated after 12 months and the relationship was determined structural changes in the myocardium of the left atrium according to contrast magnetic resonance imaging data before and after the cryoablation.Results. The severity of fibrotic myocardial lesion of the left atrium before balloon cryoablation was 1,5 [0,16; 9,3]%. In Utah patients, stage 1 fibrosis was detected in 71,4% (n=20), stage 2 in 14,3% (n=4), stage 3 in 3,6% (n=1), stage 4 in 10,7% (n=3). 3 months after cryoablation, there was an increase in the severity of fibrosis of 2,7 [1,02; 18,8]% (p<0,001). Overall efficiency of the intervention rate was 57,1%. The construction of Kaplan- Meyer curves demonstrated that the intervention was most effective in patients with minimal severity of fibrosis before ablation (Utah I) and least effective in more pronounced fibrotic lesion (stage Utah III and IV)Conclusion. Magnetic resonance imaging of the heart with contrast allows to assess fibrotic lesion of the myocardium of left atrial, which may be one of the factors of the effectiveness of interventional treatment of persistent AF.